Comparative Interpretation of the Hadith Kullu Bid‘ati Dalalah in Wahhabi and Ahlusunnah Perspectives - Moch Sulthon Zakaria (Academia Open, 2025)
General Background: The hadith Kullu Bid‘ati Dalalah (“Every innovation is misguidance”) has long been a source of debate in Islamic scholarship regarding the limits of religious innovation. Specific Background: Two influential scholars, Nasir al-Din al-Albani representing Wahhabi thought and Sayyid Muhammad bin ‘Alawi al-Maliki representing Ahlus Sunnah, offer contrasting interpretations reflecting the tension between literalism and contextualism in hadith understanding. Knowledge Gap: Previous studies have explored Wahhabi and Ahlus Sunnah theology separately, but none have comparatively analyzed their hermeneutical approaches to this specific hadith. Aim: This study examines the interpretative differences between al-Albani and al-Maliki on the hadith Kullu Bid‘ati Dalalah using Gadamer’s hermeneutical framework to reveal their theological and methodological implications. Results: The findings show that al-Albani interprets the hadith textually, rejecting all innovations as deviations, whereas al-Maliki adopts a contextual approach, distinguishing between Bid‘ah Hasanah (commendable innovation) and Bid‘ah Sayyi‘ah (blameworthy innovation). Novelty: This study uniquely integrates hermeneutical analysis with comparative theology, bridging scriptural interpretation and contemporary religious discourse. Implications: The research highlights the importance of contextual hermeneutics in promoting intellectual balance and inter-sectarian dialogue within Islamic thought. Highlights: Contrasts Wahhabi literalism with Ahlus Sunnah contextualism. Applies Gadamer’s hermeneutical theory to hadith analysis. Promotes balanced understanding and inter-sectarian dialogue. Keywords: Hadith Interpretation, Bid‘ah, Wahhabi, Ahlus Sunnah, Hermeneutics